PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT MANAJEMEN BAHAN BAKAR ANDALAN JUANDA DEPOK - Hafidza Nurul Aulia; Catur Galuh Ratnagung (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of the work environment on employee performance and determine the influence of motivation on employee performance and determine the influence of the work environment and motivation on employee performance Manajemen Bahan Bakar Andalan Juanda Depok. The method used is quantitative. The sampling technique used a saturated sample with a population of 65 respondents. Data analysis uses validity tests, reliability tests,classical assumption tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that the work environment has a significant effect on employee performance with the coefficient of determination value 53,6% and hypothesis testing is obtained values t hitung > t tabel or (8,529 > 1,998). Motivation has a significant effect on employee performance with the coefficient of determination value 52,4%, and hypothesis testing obtained values t hitung > t tabel or ( 8,323 > 1,998). The work environment and motivation simultaneously have a significant effect on employee performance using the regression equation Y = 13,314 + 0,411X1 + 0,316X2. The coefficient of determination value is 56,2%. Hypothesis test obtained value Fhitung >Ftabel or (39,853 > 2,750).